1964
DOI: 10.1063/1.1724846
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra of SiH3C≡CH and SiD3C≡CH

Abstract: Low-resolution infrared studies of silylacetylene and silylacetylene-d3 have enabled the fundamental vibrational frequencies to be assigned to normal modes of motion. Also, many of the overtone and combination bands have been tentatively asigned. Argon-matrix spectra at 4.2°K have been helpful in assigning nearly degenerate vibrations, particularly the Si–C stretching motion. Medium-resolution spectra have enabled approximate values to be obtained for the band origins and Coriolis coupling constants of most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1965
1965
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Silyl acetylene, Si&CCH, was first prepared by Ebsworth and Frankiss,l and its infra-red spectrum has been investigated?, 3 A previous study of its microwave spectrum4 indicated the C3v symmetry of the molecule and the positions of the silicon and carbon atoms, but left those of the hydrogen atoms open to doubt. In this investigation we have deduced the complete structure from rotational transitions of the following species : 28SiH312C12CHY 29SiH312C12CHY 30SiH312C12CH 28SiH313CWH, 28SiH 3 W W D , 28SiH2DWWH.…”
mentioning
confidence: 99%
“…Silyl acetylene, Si&CCH, was first prepared by Ebsworth and Frankiss,l and its infra-red spectrum has been investigated?, 3 A previous study of its microwave spectrum4 indicated the C3v symmetry of the molecule and the positions of the silicon and carbon atoms, but left those of the hydrogen atoms open to doubt. In this investigation we have deduced the complete structure from rotational transitions of the following species : 28SiH312C12CHY 29SiH312C12CHY 30SiH312C12CH 28SiH313CWH, 28SiH 3 W W D , 28SiH2DWWH.…”
mentioning
confidence: 99%